Antioxidant Agent to Improve Endometriosis Related Pain (Dysmenorrhea, Dyspareunia, Pelvic Pain): A Systematic Review and Meta-Analysis - Daud, Vanessa Pradna Adyana; Dyarma, Kadiota Rasika; Farida, Leny Silviana (Asian Journal of Health Research, 2024)
Introduction: Endometriosis is a chronic condition characterized by the presence of endometrial-like tissue outside the uterus, which causes estrogen-induced inflammation. Pelvic severe pain, dysmenorrhea, and dyspareunia are known as the most common symptoms in endometriosis patients. Antioxidants can help alleviate endometriosis-related pain. However, the mechanism is not fully understood. A study is needed to elucidate the inherent potential of an antioxidant in women with endometriosis. Material and Methods: The literature search was conducted in two databases. The outcome of interest is to measure mean changes based on pain severity using the VAS score in endometriosis-related pain, including dysmenorrhea, pelvic pain, and dyspareunia. Some of the antioxidant agents formed in this study are vitamin D, vitamin C, vitamin E, livergol (silymarin), garlic tablets, resveratrol, and melatonin compared to placebo. Meta-analysis was done using RevMan 5.4 using mean change from baseline data with their 95% confidence intervals (CI) provided. Results: Twelve studies meeting the inclusion criteria were considered relevant for assessing the potencies of antioxidants in endometriosis patients (n=695). The antioxidant group had significantly better pelvic pain improvement (MD: -2.21, 95%CI: -3.40 to -1.03, p=0.0003), reduction in dyspareunia symptoms (MD: -1.47, 95% CI: -2.68 to -0.27, p=0.02) as well as improvement in dysmenorrhea with a mean difference -1.92 (95% CI: -3.41 to -0.43, p=0.01) than the placebo group. Antioxidants showed excellent potential to be an alternative treatment in managing endometriosis-related pain, particularly pelvic pain, dyspareunia, and dysmenorrhea. Conclusion: The efficacy of antioxidant agents can be a potential treatment to alleviate pain associated with endometriosis, such as pelvic pain, dysmenorrhea, and dyspareunia.